2005
DOI: 10.2188/jea.15.1
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Daytime Sleepiness among the Japanese General Population

Abstract: BACKGROUND: Excessive daytime sleepiness is one of the principal symptoms of sleep disturbances, and is often associated with serious consequences including traffic and industrial accidents, decreased productivity, and interpersonal problems. However, there are few epidemiologic studies on excessive daytime sleepiness in a large scale sample targeting Japanese general population. METHODS: The survey was performed using a self-administered questionnaire in June 2000, targeting a population randomly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
76
3
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(96 citation statements)
references
References 23 publications
14
76
3
3
Order By: Relevance
“…The frequencies (see Table 9) were significantly different and suggest a 1.7 times greater risk of EDS for those subjects working more than 80 hours per week. An association between higher work hours in a week and EDS has been demonstrated in several studies from a number of different countries, including Canada (Hanlon et al, 2009), New Zealand (Gander et al, 2007), United States (Defoe et al, 2001;Gander et al 2007), Australia (Dorrian et al, 2006), Japan and others (Groeger, Zijlstra, & Dijk, 2004;Jagsi et al, 2008;Jewett, Dijk, Kronauer, & Dinges, 1999;Kaneita et al, 2005;Klerman & Dijk, 2005;Liu, Uchiyama, Kim, et al, 2000;Ohida et al, 2004;Skeff, Ezeji-Okoye, Pompei, & Rockson, 2004;Steinbrook, 2002).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The frequencies (see Table 9) were significantly different and suggest a 1.7 times greater risk of EDS for those subjects working more than 80 hours per week. An association between higher work hours in a week and EDS has been demonstrated in several studies from a number of different countries, including Canada (Hanlon et al, 2009), New Zealand (Gander et al, 2007), United States (Defoe et al, 2001;Gander et al 2007), Australia (Dorrian et al, 2006), Japan and others (Groeger, Zijlstra, & Dijk, 2004;Jagsi et al, 2008;Jewett, Dijk, Kronauer, & Dinges, 1999;Kaneita et al, 2005;Klerman & Dijk, 2005;Liu, Uchiyama, Kim, et al, 2000;Ohida et al, 2004;Skeff, Ezeji-Okoye, Pompei, & Rockson, 2004;Steinbrook, 2002).…”
Section: Discussionmentioning
confidence: 88%
“…The effect of inadequate sleep on EDS is well documented in resident physicians and the general population, (Dorrian et al, 2006;Groeger et al, 2004;Jewett et al, 1999;Kaneita et al, 2005;Klerman & Dijk, 2005;Liu, Uchiyama, Kim, et al, 2000;Ohida et al, 2004;Takegami, Sokejima, Yamazaki, Nakayama, & Fukuhara, 2005), but this is the first study of its kind available from India (Gupta, Pati, & Levi, 1997;Kannan, Malhotra, Bajaj, Pershad, & Chari, 1996). Suggested explanations for an association between sleepiness and work hours includes stress related to work, burnout, inadequate sleep hours, sleep deprivation and sleep debt and other work-related characteristics like floating shift work.…”
Section: Discussionmentioning
confidence: 97%
“…Factors such as fragmented sleep due to respiratory events or dyspnea have previously been related to EDS. (18,19) Among the consequences of OSAHS-related EDS is the greater frequency of traffic accidents due to drivers falling asleep at the wheel. (11) Of the patients studied, 15.3% reported having accidents the level of systemic arterial pressure was associated with obesity and with OSAHS severity.…”
Section: Discussionmentioning
confidence: 99%
“…Statistically signifiof hours of sleep. Based on the AHI, OSAHS severity was classified as mild (<15), moderate (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) or severe (>30). (14) Data were stored and analyzed using the program Statistical Package for Social Sciences, version 14.0 (SPSS Inc, Chicago, IL, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Also, surveys of the general population and the employed have reported that those who have higher stress levels have shorter sleep time (Kim et al, 2000;Nakata et al, 2004), and stronger daytime sleepiness (Kaneita et al, 2005). Studies have suggested that expectant mothers who have poor sleep may have higher stress levels.…”
Section: Introductionmentioning
confidence: 99%